"Back to Eden": An explorative qualitative study on traditional medicine use during pregnancy among selected women in Lusaka Province, Zambia. (August 2020) - El Hajj, Magalie; Sitali, Doreen Chilolo; Vwalika, Bellington; Holst, Lone
Abstract: Background and purpose: No qualitative study on traditional medicine use among Zambian pregnant women has ever been conducted. Accordingly, this study was performed to explore the perceptions, motivations and experiences of Zambian women with regard to traditional medicine use during pregnancy. Materials and methods: In-depth, semi-structured interviews were conducted in June/July 2019 with 8 adult women residing in Lusaka, Zambia, who used traditional remedies during their pregnancies, and who were recruited through purposive and snowball sampling. Results: Reported reasons behind traditional medicine use during pregnancy included labour induction, prevention of childbirth complications in case of sexual infidelity by either spouse, and prevention and/or treatment of anaemia. In addition, family members and faith leaders played an important role in influencing traditional medicine use. Conclusion: Multiple, interconnecting factors influence traditional medicine use among pregnant women in Lusaka, Zambia. Traditional medicine use during pregnancy will likely continue to be widespread across Zambia. Highlights: Reasons behind traditional medicine use among Zambian pregnant women include labour induction, and prevention of childbirth complications. Family members and community leaders play an important role in influencing traditional medicine use during pregnancy. Negative aspects associated with traditional medicine use include non-disclosure of use to medical providers, and adverse health outcomes. Positive aspects were the wide availability, the perceived fast onset of action and tolerability of traditional medicines.